Ventajas del parto vertical manifestado por embarazadas que se atienden en la sala de partos del Hospital Básico de Sucúa. Año 2015. - Silva Ortiz, Heidi Carmen (2016)
The purpose of this research was to determine the benefits of vertical delivery manifested by pregnant women who receive services at the delivery room Basic Sucúa hospital. the survey technique to 50 users that this type of delivery were performed was applied. The design used for this research was cross-sectional, descriptive, bibliographic and field. Was obtained as results in a higher percentage to 42% of pregnant women are 20 to 29 years; followed by women between the ages of 30 to 39 with 34%, a percentage of 18% under 19 and over 40 6%. Predominantly indigenous ethnic group with 64%, 34% Mestizo and Afro-Ecuadoran 2%. The level of education is at the secondary level higher percentage with 54%, followed by the top 24%, 20% primary and no 2% of women .The prevalence vertical delivery was 23.15% The advantages of birth Vertical mothers were identified by improving the frequency and effectiveness of contractions with 94%, facilitates the exit of the baby by 62%. It provides more rest between contractions with 86%. The degree of pain during childbirth was reported as moderate in 88% of women. Expulsive period was 84% less than or equal to 5 minutes and the bleeding volume was less than 250 in 84% of women in labor. It was concluded that the advantages that stand out are; less bleeding by 84%, decrease fatigue by 86%. As nursing activities educational conferences raising awareness on the benefits Childbirth Vertical and different vertical positions where brochures and an information manual pr4esentes surrendered all were made also workshops were developed.